SISTEM BANTU KELAYAKAN KAPAL PELAYARAN PADA PT ASDP KAB. KOLAKA - Qammaddin (Fakultas Teknik Universitas Lambung Mangkurat, 2017)
This research can be carried out to carry out the shipping process to avoid accidents caused by accidents caused by the use of discharges and solutions by using the approach. This auxiliary system works for purposes. The auxiliary system in this research is in the form of optimization that can overcome the problem of ship's overnight in making the voyage. Test the eligibility of ships in a good and optimal shipping to avoid fatal accident is not possible without using a good data management system and realtime. With the auxiliary system, data processing and feasibility parameters become faster and produce decisions with a high degree of accuracy. Through this research, we are able to improve the quality of ship's eligibility in shipping well in strategic and operational aspects. The research was conducted by using survey method, model and system development. The expected result is a prototype and a vessel assistive aerial system for carrying out shipping that can be implemented to address and reduce the number of marine accidents in the voyage.